Single trial ERP reading based on parallel factor analysis. (14th November 2012) - Vanderperren, Katrien; Mijović, Bogdan; Novitskiy, Nikolay; Vanrumste, Bart; Stiers, Peter; Van den Bergh, Bea R. H.; Lagae, Lieven; Sunaert, Stefan; Wagemans, Johan; Van Huffel, Sabine; De Vos, Maarten
Abstract: The extraction of task‐related single trial ERP features has recently gained much interest, in particular in simultaneous EEG‐fMRI applications. In this study, a specific decomposition known as parallel factor analysis (PARAFAC) was used, in order to retrieve the task‐related activity from the raw signals. Using visual detection task data, acquired in normal circumstances and simultaneously with fMRI, differences between distinct task‐related conditions can be captured in the trial signatures of specific PARAFAC components when applied to ERP data arranged in Channels × Time × Trials arrays, but the signatures did not correlate with the fMRI data. Despite the need for parameter tuning and careful preprocessing, the approach is shown to be successful, especially when prior knowledge about the expected ERPs is incorporated.